Do Powerful CEOs Benefit Firm Performance in Pakistan? - Kashif Arif,; Che Ruhana Isa,; Mohd Zulkhairi Mustapha, (Asian Journal of Business and Accounting, 2023)
Manuscript type: Research paper Research aims: This study examines the impact of Chief Executive Officer (CEO) power dimensions on firm performance. Design/Methodology/Approach: A panel data of 110 Pakistani firms listed on the Pakistan Stock Exchange for the period of 12 years (2008- 2019) was analysed using the GMM approach. Research findings: The GMM regression results revealed significant relationships. The analysis suggests that CEOs with considerable structural, ownership, prestige, and expert power tend to exhibit superior performance, as these factors are positively correlated with firm performance. Conversely, CEO family power appears to have no discernible impact on firm performance. Importantly, the robustness of our findings underscores the consistent nature of these relationships. Theoretical contribution/Originality: This study makes a valuable contribution to the existing literature by demonstrating the positive influence of CEO power on firm performance, which aligns with the theoretical framework of the Approach/Inhibition theory of power. The originality of this research stems from its examination of individual dimensions of CEO power and their impact on firm performance, as well as the inclusion of the additional dimension of family power. Practitioner/Policy implication: The insight from this study suggests that powerful CEO leadership is beneficial for firm performance and the concentration of power at the CEO position should be seen positively rather than the negative perspective provided by agency theory.